2020
DOI: 10.1088/1755-1315/506/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shear-Critical Reinforced Concrete Beam Blended with Fly Ash

Abstract: Results of an experimental investigation on shear-critical responses of small-scale reinforced concrete beams fabricated with normal concrete (NC) and concrete blended with supplementary materials using Class F fly ash (SMFA) are presented. The beams were reinforced with adequate stirrups as per requirement specified in design specifications. The beams were tested using Ohno beam testing setup to induce direct shear mechanisms across the shear plane. It was also intended to evaluate the shear capacity of a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Fly ash has been produced since the 1920s, and its primary components are silica (SiO 2 ), alumina (Al 2 O 3 ), iron oxide (Fe 2 O 3 ), and calcium (CaO), with varying amounts of carbon per measurement using loss on ignition (LOI) [12]. It was even significantly used in concrete (for example, USBR 1948) following the pioneering research at the University of California.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fly ash has been produced since the 1920s, and its primary components are silica (SiO 2 ), alumina (Al 2 O 3 ), iron oxide (Fe 2 O 3 ), and calcium (CaO), with varying amounts of carbon per measurement using loss on ignition (LOI) [12]. It was even significantly used in concrete (for example, USBR 1948) following the pioneering research at the University of California.…”
Section: Introductionmentioning
confidence: 99%
“…Fly ash has been proven to increase shear capacity and be safer than Portland cement [11]. Mooy et al [12], with the research about the shear capacity of fly ash and normal beam, demonstrated that the shear capacity of the fly ash beam was higher than the normal beam due to compression strength, and the crack width was smaller than the normal beam. This research is about to assess the shear behavior of two kinds of concretes, normal beam and supplementary beam, using fly ash based upon the common issue of brittle and sudden without warning shear failure due to the disturbed region with weak tensile.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this connection with internal diaphragms or external diaphragms are both advisable for 2-way frames, which can carry lateral loads from 2 horizontal directions [20]. The CFT can also be considered to be filled with cementitious materials or paste concrete such as engineered cementitious composite [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%